Peripheral Neuropathy in Mouse Models of Diabetes. Issue 3 (1st September 2016) - Jolivalt, Corinne G.; Frizzi, Katie E.; Guernsey, Lucie; Marquez, Alex; Ochoa, Joseline; Rodriguez, Maria; Calcutt, Nigel A.
Abstract: Peripheral neuropathy is a frequent complication of chronic diabetes that most commonly presents as a distal degenerative polyneuropathy with sensory loss. Around 20% to 30% of such patients may also experience neuropathic pain. The underlying pathogenic mechanisms are uncertain, and therapeutic options are limited. Rodent models of diabetes have been used for more than 40 years to study neuropathy and evaluate potential therapies. For much of this period, streptozotocin‐diabetic rats were the model of choice. The emergence of new technologies that allow relatively cheap and routine manipulations of the mouse genome has prompted increased use of mouse models of diabetes to study neuropathy. In this article, we describe the commonly used mouse models of type 1 and type 2 diabetes, and provide protocols to phenotype the structural, functional, and behavioral indices of peripheral neuropathy, with a particular emphasis on assays pertinent to the human condition. © 2016 by John Wiley & Sons, Inc.